Intersectoral conflict and delays in macroeconomic stabilization - Arslan Razmi (University of Massachusetts, Department of Economics, 2024)
An important body of literature explores the political economy reasons underlying delays in macroeconomic stabilization. This paper develops a framework to analyze conflict between two groups of economic actors, one that has an endowment of internationally tradable goods and another that is endowed with non-tradable goods. The focus is on the exchange rate policy in a developing country set-up where the government employs seigniorage revenue to finance spending pre-stabilization, and faces fiscal and balance of payments problems that necessitate stabilization with a step devaluation. The presence of exchange rate and endowment uncertainty, the role of forward-looking expectations, and the possibility of IMF aid influence the likelihood, timing, and terms of a national consensus on stabilization in interesting ways.
hdl:20.500.14394/22344
Keywords: E31; F34; F41; 330; Macroeconomic stabilization; seigniorage; inflation; devaluation; capital flight; IMF programs